2011
DOI: 10.1093/nar/gkr298
|View full text |Cite
|
Sign up to set email alerts
|

Widespread expression of piRNA-like molecules in somatic tissues

Abstract: Piwi-interacting RNA (piRNA) are small RNA abundant in the germline across animal species. In fruit flies and mice, piRNA have been implicated in maintenance of genomic integrity by transposable elements silencing. Outside of the germline, piRNA have only been found in fruit fly ovarian follicle cells. Previous studies have further reported presence of multiple piRNA-like small RNA (pilRNA) in fly heads and a small number of pilRNA have been reported in mouse tissues and in human NK cells. Here, we analyze hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
175
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(188 citation statements)
references
References 49 publications
10
175
2
1
Order By: Relevance
“…In addition to the characteristic function of the silencing of mobile elements by target slicing, piRNA function of mRNA regulation, and mechanisms of transcriptional gene silencing and mRNA deadenylation, are also described (7). Recently, studies have demonstrated that piRNAs are widely present and play important roles in somatic cells (8). However, piRNAs have not been thoroughly studied in cancers D 2 1 : 3 8 1 -3 8 8 , 2 17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the characteristic function of the silencing of mobile elements by target slicing, piRNA function of mRNA regulation, and mechanisms of transcriptional gene silencing and mRNA deadenylation, are also described (7). Recently, studies have demonstrated that piRNAs are widely present and play important roles in somatic cells (8). However, piRNAs have not been thoroughly studied in cancers D 2 1 : 3 8 1 -3 8 8 , 2 17).…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their limited expression in gonads as well as sequence diversity, piRNAs are the most mysterious subclass of sncRNAs. Although piRNAs have recently been shown to be present in somatic tissues and some human cancer cells, their functional significance is still not clear (8)(9)(10)(11). Recent studies have shown differential expression of piRNAs in gastric, liver and breast cancers (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, endogenous piRNAs also have been identified in various somatic tissues from fly, mouse, and macaque, as well as in mosquito head and thorax (22,23).…”
Section: Significancementioning
confidence: 99%
“…We and others have reported the existence of piRNA-like RNAs (pilRNAs) in both gonadal and somatic tissues (13)(14)(15)(16). However, a detailed characterization of this novel class of small RNAs expressed in somatic cells/tissues has been lacking.…”
mentioning
confidence: 99%